Investigation of parasitic infection of Merops apiaster Bird - Abdu Al- Razzaq Ahmad Abdu-Allah; Abdu-Allah Hussein Abdu-Allah (Tikrit Journal of Pure Science)
The current study was conducted in Al-Hawija district, 60 km west of Kirkuk city, and extended from September 2019 to September 2020, where 104 birds of European bee-eaters (Merops Apiaster) were collected and the results were as follows: two species of lice were diagnosed, namely Columbicola columbae and Hohorstiella lata and one species of tapeworm Rllietina tetragona. The results of the diagnosis of ectoparasites showed that the overall infection rate was 41.34%, and 14.42%for endoparasites. The results showed significant differences in the infection rates according to the different months of the study, as the highest significant infection rates were 28.57% .The results showed that weight group 41-50 gm recorded the highest rates of significant infection, with rates of 48.05 and 15.58% for Ectoparasitic and endoparasitic, respectively.